PELAKSANAAN TATA USAHA DALAM PELAYANAN ADMINISTRASI SEKOLAH DI MADRASAH - Amiroh, Tsabitah; Kanada, Rabial; Marlina, Leny; Safitri, Dian (STKIP Pesisir Selatan, 2025)
Administration plays an important role in supporting the smooth operation of schools, particularly in administrative aspects, including student and teacher data management, correspondence, and academic and financial reports. This study employs a qualitative descriptive approach, with data collection techniques including observation, in-depth interviews with administrative staff and the school principal, and a review of school administrative documents. The results indicate that the implementation of administrative tasks at MTsN 1 Ogan Ilir is generally well-managed, particularly in student data management and academic reporting. However, several challenges were identified, such as insufficient training for competency enhancement and inadequate administrative support facilities, including computers and internet connectivity. On the other hand, the school continues to make improvements through the development of a digital-based administrative system, the formulation of administrative standard operating procedures (SOPs), and enhanced coordination between administrative staff and school management. This study recommends the importance of regular training and development for administrative staff, as well as strengthening the school's management information system to improve the quality of administrative services that are effective, efficient, and accountable. These findings are expected to serve as a basis for evaluation and policy-making in the professional management of educational administration at the madrasah.